2021
DOI: 10.1186/s13059-021-02263-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimized RNA-targeting CRISPR/Cas13d technology outperforms shRNA in identifying functional circRNAs

Abstract: Short hairpin RNAs (shRNAs) are used to deplete circRNAs by targeting back-splicing junction (BSJ) sites. However, frequent discrepancies exist between shRNA-mediated circRNA knockdown and the corresponding biological effect, querying their robustness. By leveraging CRISPR/Cas13d tool and optimizing the strategy for designing single-guide RNAs against circRNA BSJ sites, we markedly enhance specificity of circRNA silencing. This specificity is validated in parallel screenings by shRNA and CRISPR/Cas13d librarie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 35 publications
2
93
0
Order By: Relevance
“…circRNAs have been implicated in human physiology and diseases, although their functions are largely unclear due to a lack of adequate methods to study them ( 39 ). Recently, CRISPR-Cas13d has been successfully applied to study the functions of circRNAs in a screening manner ( 40, 41 ), providing a novel yet efficient approach to systematically investigate circRNA functions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…circRNAs have been implicated in human physiology and diseases, although their functions are largely unclear due to a lack of adequate methods to study them ( 39 ). Recently, CRISPR-Cas13d has been successfully applied to study the functions of circRNAs in a screening manner ( 40, 41 ), providing a novel yet efficient approach to systematically investigate circRNA functions.…”
Section: Resultsmentioning
confidence: 99%
“…We first applied DeepCas13 to one circRNA screening dataset ( 40 ) where >□2500 human hepatocellular carcinoma-related circRNAs were screened. DeepCas13 successfully distinguished efficient sgRNAs from inefficient sgRNAs (Figure 3A, AUC score is 0.7492), although the area under the precision-recall curve (AUPR) was quite low for all the guides (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A guide RNA expression cassette driven by the U6 promoter was also inserted, thereby allowing both the Cas13 effector protein (Supplementary Figure S1A) and its associated guide RNA (Supplementary Figure S1B, C) to be expressed from a single plasmid. We then took advantage of simple co-transfection assays using fluorescent protein reporter genes to characterize the on-and off-target effects of each Cas13 effector, starting with RxCas13d (from Ruminococcus flavefaciens) because it is among the smallest and most commonly used Cas13 effectors (8,29,33,34,36,(45)(46)(47)(48). As diagrammed in Figure 1A, Drosophila DL1 cells were transiently transfected with the RxCas13d/guide RNA (24-nucleotide spacer length) expression plasmid along with reporter gene plasmids that express eGFP and mCherry from the copper-inducible Metallothionein A (MtnA) promoter.…”
Section: Strong Off-target Effects Can Be Observed When Rxcas13d Is Used To Deplete An Rna Of Interest In Drosophila Cellsmentioning
confidence: 99%
“…Previous studies have reported that the majority of miRNAs and lncRNAs have regulatory functions, including regulation of the evolution of stem cells, cardiomyocytes and epithelial cells, and regulation of the translation, stabilization and degradation of mRNA (15)(16)(17)(18)(19). With the development of several state-of-the-art technologies, such as the next generation of high-throughput sequencing techniques, gene silencing and gene editing, emerging evidence has demonstrated that, not only miRNAs and lncRNAs, but also circRNAs, have regulatory functions, and are associated with a variety of diseases (20)(21)(22)(23)(24). circRNAs can interact with protein complexes, RNA molecules and DNA molecules to exert their effects, and regulate a wide variety of physiological and pathological processes (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%